China's imports : impact and evaluation - Hong, Song; Villarrubia, Evan (Foreign Investment in China., 2014)
Since the beginning of reform in 1978, the Chinese import industry has expanded quickly in the wake of the rapidly growing merchandise trade. In 1978, the total value of Chinese import and export trade was USD 20.64 billion, up to 1.76069 trillion in 2006, an 84.3-fold increase. Imports alone over that period rose from USD 10.89 billion to 791.61 billion, a 71.69-fold increase. Beginning in 2003, China has been the world's third largest importer for four consecutive years. Judging from the import growth trends in recent years, it is likely that China will soon be second to only the United Stat.